Some opportunities for immunotherapy in coronavirus infection - V. S. Smirnov (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Here we review means of immunomodulatory therapy for coronavirus infection caused by SARS-CoV-2 (COVID-19). It has been appreciated that highly limited arsenal of relatively effective means and methods of prevention and treatment of the COVID-19 pandemic is available. The goal of our study was to analyze some therapeutic approaches based on available publications for COVID-19 treatment viewed from acting via innate immunity system. Convalescent plasma serotherapy represents one of the means with verified therapeutic efficacy that was accompanied with decreased viral load and relief of the disease symptoms. The drawback of serotherapy results from limited number of potential plasma donors and profound variety in amount of SARS-CoV-2-specific antibodies found in donor plasma. Another approach to COVID-19 therapy is based on using monoclonal antibodies engineered to target specific virus antigenic determinants, most often surface spike antigen. Antibodies blocking such antigen are able to prevent virus entrance into target cells and development of overt infection. On the other hand, there are monoclonal antibodies abrogating production or binding of excessive amounts of pro-inflammatory cytokines, such as IL-6, TNFα, etc., some of which (tocilizumab) have been already tested in COVID-19 therapy, whereas the remaining preparations are being currently investigated and tested. A certain breakthrough in COVID-19 therapy was provided by the well-known drugs chloroquine and dihydrochloroquine, which have proven to be effective as antiviral, anti-inflammatory and immunomodulatory means. Finally, a new multicomponent immunomodulatory preparation Cytovir-3 has been proposed already passed clinical trials and recommended for use in prevention and treatment of influenza and SARS and might have found its own niche in preventing COVID-19, as SARS-CoV-2 also belongs to the group of acute respiratory viruses. Thus, the arsenal of means for COVID-19 prevention and treatment contains the drugs for immunomodulatory therapy and prevention of immune-related disorders developing in response to invasion pathogenic viruses and lowering a risk of possible damage. Hence, correct and scientifically justified use of such remedies will increase overall effectiveness of fight against the coronavirus pandemic.